The Role of Islamic Boarding School Education in Shaping Students' Religious Character Amid the Challenges of Globalization - Mustain, Mustain; Bakar, M. Yunus Abu (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
This study aims to analyze the strategic role of Islamic boarding schools in shaping the religious character of students amid the challenges of globalization and moral crisis. Using a descriptive qualitative approach with field study methods, it is hoped that more in-depth research information can be obtained. Pesantren are understood as Islamic educational institutions that not only emphasize academic aspects but also instill spiritual and moral values through the approaches of ta'lim (teaching), ta'dib (discipline), and uswah hasanah (setting a good example). Findings indicate that educational practices in pesantren, such as congregational prayer, Quran recitation, study of classical Islamic texts, and social life based on Islamic values, are effective in instilling discipline, responsibility, and spiritual awareness. However, the implementation of character education also faces challenges, both internal, such as limited human resources, and external, such as the influence of digital media and lack of family support. Therefore, collaboration between Islamic boarding schools, families, and the community is needed so that religious character education can run optimally and sustainably. This article is expected to be a theoretical and practical reference in strengthening character education in Islamic educational institutions.